Competition Management Strategy Analysis Risk and Opportunity: Case Study of Netflix - Ridi, Ridi (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Netflix’s global expansion is another important milestone in the company’s journey. By understanding the diversity and needs of markets in different countries, Netflix not only brings its content worldwide but also invests in local content production. This is not only an expansion strategy, but also a testament to its commitment to being part of the local culture, which is key to success in the international market. In pursuing these strategies, Netflix has proven that adaptability and creativity are key to staying relevant in an ever-changing industry. Through a combination of innovation, original content production, and measured global expansion, Netflix has successfully carved out a name for itself as the undisputed leader in global digital entertainment. As the company continues to grow, future challenges and opportunities will require a continuation of the smart, flexible strategies that have been the foundation of its success to date.